2016
DOI: 10.3892/ijo.2016.3474
|View full text |Cite
|
Sign up to set email alerts
|

Unusual roles of caspase-8 in triple-negative breast cancer cell line MDA-MB-231

Abstract: Abstract. Triple-negative breast cancer (TNBC) is a clinically aggressive form of breast cancer that is unresponsive to endocrine agents or trastuzumab. TNBC accounts for ~10-20% of all breast cancer cases and represents the form with the poorest prognosis. Patients with TNBC are at higher risk of early recurrence, mainly in the lungs, brain and soft tissue, therefore, there is an urgent need for new therapies. The present study was carried out in MDA-MB-231 cells, where we assessed the role of caspase-8 (casp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Then, cells were transfected with 50 nM siNrf2 in the presence of 5 μ l Lipofectamine 2000 (Invitrogen Life Technologies, Monza, Italy) in a final volume of 1 ml serum-free medium. 67 The reaction was stopped after 5 h replacing the culture medium with fresh DMEM + 10% FBS. After 24 h from transfection, silenced cells were employed for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Then, cells were transfected with 50 nM siNrf2 in the presence of 5 μ l Lipofectamine 2000 (Invitrogen Life Technologies, Monza, Italy) in a final volume of 1 ml serum-free medium. 67 The reaction was stopped after 5 h replacing the culture medium with fresh DMEM + 10% FBS. After 24 h from transfection, silenced cells were employed for the experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Cell lysates and protein samples were prepared as previously reported (De Blasio et al, 2016). Briefly, proteins were resolved by sodium dodecyl sulfate (SDS)-polyacrylamide gel electrophoresis and transferred to a nitrocellulose membrane (Bio-Rad) for detection with primary antibodies against MCL1 (12756) and BAX (7480)…”
Section: Western Blot Analysis and Immunoprecipitationmentioning
confidence: 99%
“…Among those, CHEK1 is a checkpoint kinase that is essential for normal and cancer cells (Zhang and Hunter, 2014), GATA3 is a critical transcription factor with known oncogenic role (Mehra et al, 2005), and RAD51 has been reported as an oncogene with elevated expression in multiple cancer types including breast cancer (Maacke et al, 2000). CASP8 has multiple functions in different contexts (Stupack, 2013), with a possible essential role in breast cancer cell lines (De Blasio et al, 2016).…”
Section: Resultsmentioning
confidence: 99%